A hybrid dual‐mode dielectric resonator antenna with wide beamwidth. Issue 10 (2nd July 2020) - Yang, Ning; Weng, Zibin; Wang, Lei; Liao, Tao
Abstract: A wide beamwidth rectangular dielectric resonator antenna (RDRA) working on dual modes is proposed in this letter. The radiator of the antenna with inside metallic posts and outside metallic walls is placed on a groundplane with a size of 2 λ g × 2 λ g . A TE ′ δ 21 TE′δ21 mode, which is similar to TE δ 21 mode, is generated by using the metallic posts inside the DR. By adjusting the height of metallic posts and the distance between the DRA and the metallic walls, the TE ′ δ 21 mode, and the TE δ 11 mode are superimposed with each other, widening the beamwidth of the RDRA to above 140° in both the E‐plane and H‐plane. This antenna works from 8.1 to 8.7 GHz with a relative bandwidth of 7.1%, which can be a good candidate in navigational systems.